The Influence of the Habit of Reading the Qur'an on the Peace of Mind of Class X Students at SMAIT Tri Sukses Generus Balikpapan - Jihan Noor Annisa; Iskandar Yusuf (Universitas Dharmawangsa Medan, 2025)
In contemporary life, especially during adolescence, the need for inner peace has become increasingly important. Engaging in reading the Qur'an is seen as a spiritual practice that is considered to foster tranquility. This study seeks to assess the impact of the habit of reading the Qur'an on students' mental calm. This study uses a quantitative descriptive methodology through a survey approach. This study involved 30 students of class X of SMAIT Tri Sukses Generus Balikpapan, selected using the total sample method. The data collection tool used a 4-point Likert scale questionnaire and was analyzed through a basic descriptive statistical method. The results of the study show that the habit of reading the Qur'an is categorized as sufficient, while the peace of mind of students is also classified as sufficient. This signifies that, although the habit of reading the Qur'an is not entirely habitual or ideal, it contributes positively to emotional stability and inner calm. Engaging in the recitation of the Qur'an has been shown to improve the formation of religious character and psychological balance among students. This study is expected to be a reference for educational institutions in fostering the habit of reading the Qur'an as an integral component of character development programs.